Analysis of the need for development of process oriented guided inquiry learning (POGIL) learning tools in natural science learning in junior high schools - D Fatmawati; Sajidan Sajidan; N Y Indriyanti (Pascasarjana Universitas Pendidikan Indonesia, 2021)
This study aims to analyze the needs of developing science-oriented process learning guided inquiry (POGIL) learning tools in junior high schools. The study population included state junior high schools in the Surakarta district in the 2019/2020 school year. The research sample was determined by purposive sampling technique by considering, school status, UN scores. The number of sample schools is 3 grade 7 at three schools in Surakarta, each from medium and low high schools in Surakarta. Research data collected by interview, observation, and analyzed descriptively. The results of the study show: Schools face several obstacles and constraints, namely limited operational support, and the conversion of laboratory functions into classrooms